Analysis of the Number of Pregnant Women Suffering from Chronic Energy Deficiency (CED) in Palu City - Evi Fitriani; Wiwid Arsanda (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Chronic Energy Deficiency (CED) among pregnant women is a significant public health problem with serious consequences for both maternal and fetal health. In Indonesia, the prevalence of CED remains relatively high, particularly in areas with limited access to health services, inadequate nutritional intake, and socio-economic constraints. Objective: This study aims to describe the distribution of pregnant women affected by Chronic Energy Deficiency in Palu City during the period 2023–2024, based on secondary data obtained from the Central Statistics Agency of Palu City. Method: A quantitative descriptive method was employed by analyzing secondary data sourced from the Central Bureau of Statistics of Central Sulawesi Province. The data analyzed included the number of pregnant women diagnosed with Chronic Energy Deficiency. Data analysis was conducted by compiling the information into graphical presentations and interpreting the observed patterns and trends narratively. Results: The findings indicate fluctuations in the number of pregnant women experiencing Chronic Energy Deficiency between 2023 and 2024. A decline in the number of CED cases was observed from 2023 to 2024. Geographical factors, limited availability of health facilities, and socio-cultural influences are considered to be the main contributors to the observed trends. Conclusion: Chronic Energy Deficiency before and during pregnancy increases the risk of adverse pregnancy outcomes, including low birth weight. Although annual variations were observed, the consistently recorded number of pregnant women affected by CED underscores the urgent need for sustained and targeted interventions, particularly in areas with limited access to health services.